Understanding the molecular regulatory mechanisms of autophagy in lung disease pathogenesis - Lin, Lin; Lin, Yumeng; Han, Zhongyu; Wang, Ke; Zhou, Shuwei; Wang, Zhanzhan; Wang, Siyu; Chen, Haoran (Frontiers in Immunology, 2024)
Lung disease development involves multiple cellular processes, including inflammation, cell death, and proliferation. Research increasingly indicates that autophagy and its regulatory proteins can influence inflammation, programmed cell death, cell proliferation, and innate immune responses. Autophagy plays a vital role in the maintenance of homeostasis and the adaptation of eukaryotic cells to stress by enabling the chelation, transport, and degradation of subcellular components, including proteins and organelles. This process is essential for sustaining cellular balance and ensuring the health of the mitochondrial population. Recent studies have begun to explore the connection between autophagy and the development of different lung diseases. This article reviews the latest findings on the molecular regulatory mechanisms of autophagy in lung diseases, with an emphasis on potential targeted therapies for autophagy.